Pengaruh Permainan Bowling Bergambar Angka Terhadap Keterampilan Kognitif Anak Usia Dini - Nostalgianti Citra; Pascalian Hadi Pradana; Nabilah Nabilah; Ade Irma N (Journal of Elementary School (JOES), 2022)
This research is carried out in order to find out whether there is an influence or impact on the number-illustrated bowling game on the cognitive skills of early childhood at Nurus Sa'adah Kindergarten 03 Paluombo hamlet, Sumbersalak village, Ledokombo district. The technique used as a reference in data collection is to use the method of observation (observation) and documentation. The population in this research is as many as 20. Determination of the sample randomly with the sampling technique is not random. Pre-experimental research design Pretest-posttest design for the group. The analysis method uses simple regression and the number of samples used is N = 20 students. The results of this research indicate that Ha is accepted and H0 is rejected. Based on the results of this research, it shows that there is a significant effect of bowling with numbers on the cognitive skills of early childhood.